Implant supported prosthesis on edentulous mandible with multiple impacted teeth - a case report with 5 year follow up - Annapoorni Hariharan; Siva Prakash Dhanaraj (Wolters Kluwer Medknow Publications, 2019)
Multiple impacted teeth are quite often syndromically related, which could be hormonal or metabolic. It may be also due to infection, cyst, or trauma. A number of idiopathic multiple impacted teeth cases have been reported in the literature. In most of these situations, the impacted teeth are few in number. Here, we present a case with all mandibular teeth impacted. The number of reports in the literature of rehabilitation of such a clinical situation is very less. Impacted teeth can significantly complicate the rehabilitation of an otherwise straight forward case. When all teeth are impacted, the situation becomes even more complex. This case report illustrates prosthodontic rehabilitation of mandibular arch of a 24-year-old, asyndromic patient with implant-retained dentures following the surgical removal of impacted teeth. The objective of presenting this clinical report is primarily to increase the awareness, with which, the rehabilitation can be handled in a similar situation and also for the fact that such a report is a rarity.